Strategi Pemberdayaan Masyarakat oleh Fasilitator Puspaga dalam Pencegahan Kekerasan Perempuan dan Anak serta Pembentukan Keluarga Berkualitas Kelurahan Ketabang - Lesanti, Putri; Muljanto, Muhammad Agus (IAI Nasional Laa Roiba Bogor, 2024)
Family is an important aspect in the formation of individual character in a family. Prosperous and quality families form quality generation as well. To form a prosperous and quality family, insight or knowledge that is open and following the times is needed. Surabaya City is a city with a child-friendly city category and prioritizes gender equality against sexual violence against children and women. To make it happen, the Surabaya City Government under the auspices of the Office of Women's Empowerment and Child Protection and Population Control and Family Planning or DP3APPKB Surabaya City established the PUSPAGA (Family Learning Center) program to support efforts to form a prosperous and quality family The form is to place PUSPAGA facilitators in each Rw hall spread across 94 points in the city of Surabaya. The research used was quality research with a type of descriptive research, the purpose of this study was to determine the empowerment strategy carried out by the facilitator of the Rw 3 hall in Ketabang Village